MUHAMMADIYAH’S UṢŪL AL-FIQH IN DETERMINING THE BEGINNING OF RAMAḌȂN AND SYAWWȂL MONTHS - Ahwan Fanani; Tholkhatul Khoir; Shahrin bin Hashim (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
The different determination of the beginning of Ramaḍȃn and Syawwȃl by Muhammadiyah whis is frequently different from that by The Government has spark heat debat in Indonesian society. The difference stems from criteria used by both Muhammadiyah and Indonesian Government. Muhammadiyah emphasizes the use of the hisȃb as solely media for determining the coming of new Hegira month, while Indonesian government sticks on imkȃn al-ru‘ya, a mix between hisȃb and ru’ya. As a renewal Islamic organization, Muhammadiyah do not belong to any traditional Islamic schools of law, rather it refers directly to Quran and prophet tradition. The use hisȃb, however, is not explicitly stated by both sources, but it is inferred from various Quranic verses. This study aims to describe the uṣūl al-fiqh of Muhammadiyah and and to reveal the use of it in validating the criteria for determining the coming of Ramaḍȃn dan Syawwȃl months. The article is based on qualitative research from interview and literary sources. Data analysis was carried out through data condensation, data display and drawing conclusions and verification. This study shows that the uṣūl al-fiqh of Muhammadiyah is contained in and is part of the Manhaj Tarjih. Manhaj Tarjih is not a configuration of uṣūl al-fiqh rather a religious perspective of Muhammadiyah to deal with religious issues. Uṣūl al-fiqh of Muhammadiyah has not been completely structured, but several basic elements of uṣūl al-fiqh are already in it. The use of hisȃb by Muhammadiyah, both in wujūd al-hilȃl approach or the Integrated Global Hijri Calendar is based on the verses of the Qur'an, the scrutiny of ‘illa (ratio legis/ legal reason) of ḥadīṡ on ru‘ya and the application of uṣūl al-fiqh principles of deductions. The uṣūl al-fiqh employed by Muhammadiyah ini the determination of the coming of Ramaḍȃn and Syawwȃl are based on conventional uṣūl al-fiqh principles, but it chooses specific principles that that allow for adjustments to determine the beginning of Ramaḍȃn and Syawwȃl.